If We Don't Watch Where We're Going, We Might Not Like Where We Go: School Reform at the Turn of the 21st Century - Van Dempsey (Educational Considerations, 2003)
American education appears to be fascinated with educational reform. The 20th century could be marked in school reform initiatives that would note the passing of time as well as any calendar. Cuban (1990) documented this obsession with reform before the most recent version, No Child Left Behind, was at full speed.